The forms and functions of modal verbs in sections of the English tourism research articles - Domínguez Morales, María Elena (Estudios de lingüística aplicada, 2023)
Resumen (revisado) The tourism research article (RA) has not been the focus of many studies. This volume offers a description of the genre in terms of section, besides an analysis of the most used language features in each section of the RA. Among these are the presence of modal verbs. Precisely, the goal of this work is to describe their use, meaning and functions in a corpus of the "introduction" and "conclusion" sections of the RA in tourist studies. The compilations included texts from leading journals in the area. The method of inquiry includes corpus linguistics tools to analyze texts as well as specific examples to show how these forms behave in the RAs. The analysis of context is also essential in order to identify the exact meanings of modal verbs, and for that reason visual inspection of each sample is mandatory. The discussion of the evidence obtained is accounted for by studies in the domain of functional linguistics. The conclusions show that formal variation exists in the introduction and the conclusion sections.This also applies to their meanings. Dynamic modality is attested to be more recurrent in the introductions and epistemic modality is preferred in the concluding sections. The functions performed by these modals are varied to feature interpersonal and textual cues in the elaboration of meaning in the RA.